A Friendship Ex Libris – Karl Wolfskehl, Salman Schocken, and their Libraries. Issue 1 (16th August 2022) - Schneidawind, Julia
Abstract: The following article explores the question of how the biographies of the two German-Jewish collectors and bibliophiles Karl Wolfskehl and Salman Schocken are still connected today through their book collections. Schocken acquired Wolfskehl's library in 1937, not only enabling Wolfskehl to go into exile, but also saving the approximately 3, 000-volume collection from destruction. The article traces the origins and development of both libraries in the context of Wolfskehl's and Schocken's lives with reference to their individual understanding of collecting, and discusses how the sale of the collection led to a friendly, if not uncomplicated, long-term connection between the two, which can still be traced through their books and libraries today.